Application Of Accounting System As A Form Of Internal Control In Employee Payroll At PT Andika Pratama Abadi - Diana Afriani; Denny Salim; Stefvy (Journal of Creative Power and Ambition (JCPA), 2026)
This research was conducted at PT Andika Pratama Abadi. The purpose of this research is to determine the effectiveness of internal control activities in the payroll cycle at PT. Andika Pratama Abadi. This type of research is descriptive research by analyzing the elements of internal control at PT Andika Pratama Abadi, such as the control activities of the payroll system, and compare the company's payroll system with an appropriate payroll system. The data collected is secondary data, including the payroll system and other information from the company related to this research. The results show that the analysis of the payroll accounting system at PT. Andika Pratama Abadi indicates significant internal control weaknesses that hinder the efficiency and reliability of the payroll process. There is a lack of proper separation of duties, which increases the risk of errors and fraudulent activities. The manual process is prone to human error. Manual data entry can lead to errors, omissions, or deliberate manipulation of data. The lack of verification can result in undetected errors or fraud. There appears to be no clear authorization control. Handling of physical documents poses a risk if not properly secured